Kocher-Debre-Semelaigne Syndrome: Response to Thyroxine Replacement Therapy - Vishal V Tewari; Ritu Mehta; Kunal Tewari (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2016)
Introduction: Congenital hypothyroidism with muscular pseudohypertrophy or Kocher- ebre- Semelaigne syndrome is the result of long standing untreated moderate to severe ypothyroidism. The pathogenesis of this muscular pseudohypertrophy is unknown and it is usually noted in the muscles of the extremities, limb girdle, trunk, hand and feet but is most evident in the muscles of the lower limb giving the child a Herculean appearance. This is in contrast to the thyroid myopathy due to hypothyroidism in older age group patients which results in muscle atrophy and wasting. Case: A 6-year-old male child presented with short stature, globally delayed developmental milestones, a characteristic stocky and muscular appearance due to hypertrophied back and calf muscles. Investigations revealed delayed osseous maturation, elevated total cholesterol with low T3 and T4 with grossly elevated TSH. He was diagnosed as a case of congenital hypothyroidism with muscular pseudohypertrophy and thyroxine replacement therapy was initiated. A rare presentation of congenital hypothyroidism with muscular pseudohypertrtophy i.e. Kocher-Debre-Semelaigne syndrome and dramatic response to therapy with thyroxine replacement with regression of the muscular pseudohypertrophy is discussed.  Conclusion: Prolonged untreated congenital hypothyroidism results in pseudohypertrophy of muscles of limbs and trunk. There is muscle weakness, stiffness and sluggish deep tendon jerks. Laboratory parameters show deranged thyroid function tests, elevated creatinine kinase and a myopathic pattern on electromyogram. Thyroxine replacement therapy rapidly results in regression of the pseudohypertrophy with improvement in muscle power and reduction in stiffness. Our case showed all the phenotypic and metabolic features of this syndrome with rapid resolution of muscle pseudohypertrophy with thyroxine replacement.